Effect and safety of perioperative ketamine/esketamine administration on postoperative pain and depression after breast cancer surgery: a systematic review and meta-analysis - Sun, Xinyi; Li, Chengwei; Xu, Lin; Lin, Xiaojie; Zhang, Zheng; Lin, Chunlong; Li, Jianjun; Wei, Penghui (Frontiers in Pharmacology, 2025)
BackgroundPatients with breast cancer experience varying degrees of pain, depression, and anxiety after surgery, which affect their postoperative recovery. Although ketamine/esketamine exhibit potential for opioid-sparing and controlling postoperative pain and depression, their effects on postoperative pain and depression remain unclear. This meta-analysis aimed to evaluate whether perioperative administration of ketamine/esketamine could reduce postoperative pain and depression, improve postoperative recovery, and reduce the incidence of adverse events in patients after breast cancer surgery.Material and methodsPubMed, Embase, Web of Science, Cochrane Library, and Clinical Trials were searched from inception until June 2, 2024 for randomized controlled trials in English language on the effect of perioperative ketamine/esketamine on postoperative pain in patients undergoing breast cancer surgery. The primary outcome was the postoperative pain score, and the secondary outcomes were the postoperative depression score, quality of postoperative recovery, incidence of adverse events, and extubation time. The standardized mean difference and 95% confidence interval (CI) were calculated for continuous outcomes, and the risk ratio and 95% CI were calculated for binary variables.ResultsSeven studies involving 748 patients were included in this meta-analysis. No significant differences were found in postoperative pain scores at 2 h, 4 h, 1 day, 3 days, 7 days, and 3 months after surgery. Postoperative depression scores at 3 and 7 days after surgery were lower in the ketamine/esketamine group. The incidence of dizziness was lower in ketamine/esketamine group. No statistically significant differences were observed in postoperative depression scores at 30 days after surgery, quality of postoperative recovery at 1 and 3 days after surgery, extubation time, or the incidence of nausea, vomiting, and nightmares.ConclusionPerioperative ketamine/esketamine administration did not significantly reduce postoperative pain in patients undergoing breast cancer surgery; however, it may reduce depression within a short period after the surgery.Clinical Trial Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42024572414, identifier CRD42024572414.